A simple transmit diversity technique for wireless communications. - Alamouti, S.M.
This paper presents a simple two-branch transmit diversity scheme. Using two transmit antennas and one receive antenna the scheme provides the same diversity order as maximal-ratio receiver combining (MRRC) with one transmit antenna, and two receive antennas. It is also shown that the scheme may easily be generalized to two transmit antennas and M receive antennas to provide a diversity order of 2M. The new scheme does not require any bandwidth expansion or any feedback from the receiver to the transmitter and its computation complexity is similar to MRRC
Keywords: Cellular communications; Computation complexity; Diversity order; Maximal-ratio receiver combining; Receive antenna; Transmit antennas; Two-branch transmit diversity; Wireless communications